Reducing inequities in maternal and child health in rural Guatemala through the CBIO+ Approach of Curamericas: 8. Impact on women's empowerment - Ira Stollak; Mario Valdez; William T. Story; Henry B. Perry (BMC, 2023)
Abstract Background Indigenous Maya women in the rural highlands of Guatemala have traditionally faced constraints to decision-making and participation in community affairs. Anecdotal experiences from previous Curamericas Global projects in Guatemala and Liberia have suggested that interventions using the CBIO+ Approach (which consists of implementing together the Census-Based, Impact-Oriented Approach, the Care Group Approach, and Community Birthing Centers), can be empowering and can facilitate improvements in maternal and child health. This paper, the eighth in a series of 10 papers examining the effectiveness of CBIO+ in improving the health and well-being of mothers and children in an isolated mountainous rural area of the Department of Huehuetenango, explores changes in women's empowerment among mothers of young children associated with the Curamericas/Guatemala Maternal and Child Health Project, 2011-2015. Methods Knowledge, practice, and coverage (KPC) surveys and focus group discussions (FGDs) were used to explore six indicators of women's empowerment focusing on participation in health-related decision-making and participation in community meetings. KPC surveys were conducted at baseline (January 2012) and endline (June 2015) using standard stratified cluster sampling. Seventeen FGDs (9 with women, 3 with men, 2 with mothers-in-law, and 3 with health committees), approximately 120 people in all, were conducted to obtain opinions about changes in empowerment and to identify and assess qualitative factors that facilitate and/or impede women's empowerment. Results The KPC surveys revealed﻿ statistically significant increases in women's active participation in community meetings. Women also reported statistically significant increases in rates of participation in health-related decision-making. Further, the findings show a dose-response effect for two of the six empowerment indicators. The qualitative findings from FGDs show that the Project accelerated progress in increasing women's empowerment though women still face major barriers in accessing needed health care services for themselves and their children. Conclusion The Project achieved some notable improvements in women's decision-making autonomy and participation in community activities. These improvements often translated into making decisions to practice recommended health behaviors. Traditional cultural norms and the barriers to accessing needed health services are not easily overcome, even when empowerment strategies are effective.